Pengaruh COVID-19 Pada Kehamilan Trimester III Di Ruang Aster COVID-19 RSUD Tangerang Periode Februari 2022 - Ana Ruliana; Maryati Sutarno (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Background: COVID-19 is a disease caused by SARS-CoV2 which attacks the respiratory tract acutely which can be transmitted from human to human with symptoms of respiratory disease ranging from mild to moderate and can recover without special treatment or care. Especially pregnant women are a group that is vulnerable to health problems, especially infectious diseases due to changes in body physiology and immune response mechanisms in their bodies so that they can be greatly affected by some respiratory infections. The purpose of the study: to determine the effect of Covid-19 on third trimester pregnancy in the Covid-19 Aster Room at Tangerang Hospital. Research Methods: This study used a cross sectional approach. The population in this study were 189 pregnant women who were treated in the Aster Covid-19 RSUD Tangerang in 2021. The sample in this study were all pregnant women in the third trimester with a diagnosis of Covid-19 and treated in the Aster room of the Tangerang Regional Hospital in 2021, with a total of 84 respondents. The data were analyzed using the chi square test. Research results: From the results of the impact of Covid-19 on pregnant women in the third trimester, it is known that of the 84 respondents, most of them had a covid effect of 78 respondents (92.9%) and the rest had no effect, i.e. if the pregnant women returned home recovering or gave birth normally & term of 6 respondents (7.1%). Conclusions and Suggestions: There is no relationship between age, education, occupation, gravida, ANC visits and the environment with the effect of covid-19 on third trimester pregnancy at Tangerang Hospital in 2022. Pregnant women are advised to seek more information about pregnancy care through health workers especially midwives, posyandu officers, mass media and others, so that they can recognize the risks of pregnancy, especially those confirmed by COVID-19